THAT’S A CONSTRUCTION FOR YOU/LAS CONSTRUCCIONES ES LO QUE TIENE(N): GRAMMATICALIZATION VIA SUBJECTIFICATION IN ATTRIBUTIVE CLAUSES IN ENGLISH AND SPANISH - Gonzalez Garcia, Francisco (International Journal of English Studies, 2009)
This paper deals with matrix copular inferentials of the type “That’s love for you” and “El amor es lo que tiene”. Specifically, it shows that these configurations exhibit an early stage of grammaticalization, characterized by an increase in pragmatic significance and subjective expressiveness. It also demonstrates that the semantico-pragmatic (including discoursefunctional) properties of these constructions in English and Spanish lend further credence to the Traugottian context-based view of grammaticalization as involving two distinct yet related subtypes. The first one, pragmatic strengthening, is argued here to give rise to a shift from identifying attribution to characterizing attribution, thus expressing a positive or negative evaluation by the subject/speaker regarding the entity/person encoded in the lexical filler. The second one, at a textual level, results in these constructions functioning as summative discourse markers.Moreover, this paper offers a constructionist overview of the place of these inferential constructions within the family of focusing constructions.